Synthesis and Characterization of Some New Metal Complexes of (5-C-Dimethyl Malonyl-Pentulose-Î³Lactone-2,3-Enedibenzoate) - Mukhlis, A-J. A.; Sarhan, B. M.; Rumez, R. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The synthesis of complexes for (Ca+2, Co+2, Ni+2, Cu+2, Zn+2, Cd+2 and Hg+2) with new ligand (5-C-dimethyl malonyl-pentulose-Î³-lactone-2,3-enedibenzoate) (L) have been successfully prepared and characterized by (1H and 13CNMR, FTIR, (U.V-Vis) spectroscopy, Atomic absorption spectrophotometer (A.A.s), Molar conductivity measurements and Magnetic moment measurements, and the following general formula has been given for the prepared complexes [M(L)Cl2] where M = (Ca+2, Co+2, Ni+2, Cu+2, Zn+2, Cd+2, Hg+2),  L = (5-C-dimethyl malonyl-pentulose-Î³-lactone-2,3-enedibenzoate).